Simulation and Experiment of Optimal Load Matching for Hydraulic Quadruped Robot - SHAO Junpeng; LIU Mengmeng; SUN Guitao (Journal of Harbin University of Science and Technology)
Aiming at the problem of low efficiency and poor response speed of hydraulic quadruped robot, the method of joint trajectory and optimal load matching in robot square gait is studied in depth, the 3D model of the hydraulic quadruped robot established, and the kinematics analysis carried out, the joint driving function under the squat gait of the robot is obtained The robot dynamics simulation analysis is carried out, and the joint trajectory of the power mechanism is obtained The optimal matching parameters of robot dynamic mechanism are obtained by establishing optimal load matching Finally, the idea was verified by AMEsim simulation and robot prototype test. The results show that under the condition of load, when the pressure of fuel supply is 17Mp, the noload flow of servo valve is 77L/min and the diameter of piston is 26mm, the working efficiency of power mechanism is high, and the response speed is fast, The effectiveness of the method is verified